2014
DOI: 10.1093/geront/gnt162
|View full text |Cite
|
Sign up to set email alerts
|

Normal Aging or Depression? A Qualitative Study on the Differences Between Subsyndromal Depression and Depression in Very Old People

Abstract: The results might indicate that SSD in very old people is not related to pathology but to normal aging, even though the condition correlates with negative health parameters. Overlooking certain psychosocial aspects of living in the very old may pose a risk of both underdiagnosis and overdiagnosis in the spectrum of depressive disorders.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
30
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(32 citation statements)
references
References 45 publications
0
30
0
1
Order By: Relevance
“…This phenomenon, known as "depression without sadness" or "masked depression" may lead to misdiagnosis (Covinsky et al 2014). A lack of consensus on how to classify subsyndromal depressive symptoms or depressive presentations that are atypical may lead to misindentification of these syndromes (Ludvigsson et al 2014). Furthermore, somatic elements which are prevalent in old age (e.g., physical disability, functional limitations, fatigue, digestive problems, and physical pain) may also cause emotional distress, leading to a clinical picture that, in some ways, resembles a depressive syndrome.…”
Section: Depressionmentioning
confidence: 99%
“…This phenomenon, known as "depression without sadness" or "masked depression" may lead to misdiagnosis (Covinsky et al 2014). A lack of consensus on how to classify subsyndromal depressive symptoms or depressive presentations that are atypical may lead to misindentification of these syndromes (Ludvigsson et al 2014). Furthermore, somatic elements which are prevalent in old age (e.g., physical disability, functional limitations, fatigue, digestive problems, and physical pain) may also cause emotional distress, leading to a clinical picture that, in some ways, resembles a depressive syndrome.…”
Section: Depressionmentioning
confidence: 99%
“…Groups of older adults with SSD include those evolving into or remitting from major depression, [10, 11] those with a chronic course of SSD that may be accompanied by functional limitations and low perceived social support, [1113] and others who may experience SSD in the context of natural conditions and psychological and physiological processes in very late life. [13] Thus, the fate of older individuals with SSD may be varied and disease processes underlying the association of SSD and cognitive decline are not well understood.…”
Section: Introductionmentioning
confidence: 99%
“…19,20 Recently, several studies examined empirically derived long-term courses of late-life depressive symptoms based on symptom scales [21][22][23][24][25] and found that 3% to 11% of the older population experience chronically high levels of depressive symptoms during ageing. For the latter group, depressive symptoms may be manifestations of physical illness, normal ageing, or neurodegeneration.…”
Section: Introductionmentioning
confidence: 99%